The Optimal Taxation of Dividends in a Small Open Economy - Clemens Fuest; Bernd Huber (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper analyses the optimal taxation of dividends and other types of income from portfolio investment. We show that, in an open economy, it is not desirable to offer double taxation relief for dividends paid by domestic firms to domestic households. This result holds for fairly general utility functions. The reason is that the marginal shareholder in domestic firms is a foreign investor. This implies that the level of real investment is not affected by the taxation of domestic dividend income at the household level. A reduction of the tax burden on dividends is therefore merely an undesirable subsidy on domestic asset holdings. Our results also extend the literature on the optimal taxation of risky asset income in general.
Keywords: 330; Dividends; international taxation; portfolio investment